The issue of standardization of interventional medical technologies in modern cardiology - I. Yu. Karpenko; Mohamed Hanafi (Kazimierz Wielki University, 2017)
The purpose of the study was to assess the experience of implementing local protocols for the standardization of interventional medical technologies at the regional clinical hospital. There was demonstrated that the implementation of local clinical protocols can reduce the number of misdiagnoses, the total number of clinical and instrumental and clinical-laboratory studies, duration of in-hospital stay. The resynchronization of myocardial contraction by means of biventricular cardiostimulation, regulated by the clinical protocol, allows to achieve significant clinical effect on parameters such as ultimate diastolic pressure in the LV, the area of mitral regurgitation, the functional class on HYHA